Kulturowa faza rozwoju społeczeństwa a realizacja perspektywicznego wzorca konsumpcji - Piasny, Janusz; Sołtysiak, Jan (Wydział Prawa i Administracji UAM, 1976)
The contemporary human needs exceed the limits of reproduction. Therefore they can be easily steered. First of all the steering bodies should develop the needs belonging the broadly considered cultural sphere. It seems to be advantageous from the economic, sociological and ideological point of view.
The Cultural Phase of Social Development and the Reality of the Long — Term Consumption Pattern